2022
DOI: 10.3389/fvets.2022.899951
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship Between Cardiac Function and Insulin Sensitivity in Horses: A Pilot Study

Abstract: Metabolic syndrome in humans is commonly associated with cardiovascular dysfunction, including atrial fibrillation and left ventricular diastolic dysfunction. Although many differences exist between human and equine metabolic syndrome, both of these conditions share some degree of insulin resistance. The aims of this pilot study were to investigate the relationship between insulin sensitivity and cardiac function. Seven horses (five mares, two geldings, aged 17.2 ± 4.2 years, weight 524 ± 73 kg) underwent insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…In contrast, the clinical relevance of hypertension (important in human metabolic syndrome) remains to be documented in donkeys. In laminitis-prone ponies on summer pastures and in horses with metabolic syndrome after insulin infusion, it has been observed that there is an increase in blood pressure [41,42].…”
Section: Clinical Signsmentioning
confidence: 99%
“…In contrast, the clinical relevance of hypertension (important in human metabolic syndrome) remains to be documented in donkeys. In laminitis-prone ponies on summer pastures and in horses with metabolic syndrome after insulin infusion, it has been observed that there is an increase in blood pressure [41,42].…”
Section: Clinical Signsmentioning
confidence: 99%